Biocompatibility of intraocular lens power adjustment using a femtosecond laser in a rabbit model. Issue 8 (August 2017) - Werner, Liliana; Ludlow, Jason; Nguyen, Jason; Aliancy, Joah; Ha, Larry; Masino, Bryan; Enright, Sean; Alley, Ray K.; Sahler, Ruth; Mamalis, Nick
Abstract : Purpose : To evaluate the biocompatibility (uveal and capsular) of intraocular lens (IOL) power adjustment by a femtosecond laser obtained through increased hydrophilicity of targeted areas within the optic, creating the ability to build a refractive‐index shaping lens within an existing IOL. Setting : John A. Moran Eye Center, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Six rabbits had phacoemulsification with bilateral implantation of a commercially available hydrophobic acrylic IOL. The postoperative power adjustment was performed 2 weeks after implantation in 1 eye of each rabbit. The animals were followed clinically for an additional 2 weeks and then killed humanely. Their globes were enucleated and bisected coronally just anterior to the equator for gross examination from the Miyake‐Apple view to assess capsular bag opacification. After IOL explantation for power measurements, the globes were sectioned and processed for standard histopathology. Results : Slitlamp examinations performed after the laser treatments showed the formation of small gas bubbles behind the lenses that disappeared within a few hours. No postoperative inflammation or toxicity was observed in the treated eyes, and postoperative outcomes and histopathological examination results were similar to those in untreated eyes. The power measurements showed that the change in power obtained was consistent and within ±0.1 diopter of the target. Conclusions : Consistent and precise power changes can be induced in the optic of commercially available IOLs in vivo by using a femtosecond laser to create a refractive‐index shaping lens. The laser treatment of the IOLs was biocompatible.